Managing Headwater Conservation For Environmental Stability: Ecological Communication And Resilience In The Sumber Brantas Arboretum, Indonesia - Utami, Muherni Asri; Hina, Shahzadi (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
The Sumber Brantas Arboretum in Batu City serves as the Upstream or Zero Point of the Brantas River, impacting 16 cities and regencies in East Java. Therefore, the traditional ecological knowledge of the local community is crucial for preserving this area. As the river's primary source, environmental communication in Batu City must be improved to foster local environmental stewardship. This descriptive research views the world through constructivism using qualitative methods. It explores the management of the Arboretum's nature reserve to ensure environmentalism stability, utilizing theories of ecological communication and resilience. Researchers employed in-depth observations and interviews with purposive sampling, specifically targeting officials from Perum Jasa Tirta I. Data analysis followed Creswell’s techniques. The study concludes that the Sumber Brantas Arboretum is a strategic socio-ecological system vital for the Brantas Watershed's stability. This is achieved through the integration of upstream conservation, vegetation management, institutional governance, and adaptive environmental communication. Consequently, the Arboretum's environmental stability is not a static condition but the result of a dynamic process of adaptive management connecting ecological, social, cultural, and policy dimensions within a resilient system.